Sodiophilicity-Enhanced Modified Carbon Black and Method for Manufacturing the Same
A modified carbon black coating layer addresses the interfacial resistance issue in sodium batteries by improving wettability and reducing sheet resistance, thereby enhancing electrochemical performance and stability.
Patent Information
- Application Number
- KR1020250011730
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2024-11-13
- Filing Date
- 2025-01-24
- Publication Date
- 2026-11-05
- Estimated Expiration
- 2045-01-24
AI Technical Summary
The high interfacial contact resistance between sodium metal and solid electrolytes in sodium rechargeable batteries limits their efficiency and lifespan due to restricted metal cation movement, necessitating improved wettability and reduced sheet resistance.
A modified carbon black coating layer is manufactured by heat-treating carbon black powder to remove surface chemical bonds, forming a slurry with a solvent, and applying it onto a substrate to enhance sodium wettability and reduce sheet resistance.
The modified carbon black coating layer significantly improves electrochemical performance by reducing the contact angle and sheet resistance, enhancing sodium ion transmission and battery stability.
Smart Images

Figure 112025010527770-PAT00005_ABST
Abstract
Description
Technology Field
[0001] The present invention relates to modified carbon black, and more specifically, to modified carbon black with improved sodium wettability and a method for manufacturing the same. Background Technology
[0002] Although extensive research has been conducted on lithium-ion batteries to date, there is a growing need to develop new battery systems in consideration of the limited availability of lithium mineral resources and cost-effectiveness. In this regard, sodium-based rechargeable batteries, which possess abundant resource reserves, are attracting attention. While sodium rechargeable batteries offer the advantages of resource abundance and low cost, they present challenges such as lower energy density and limited electrochemical stability compared to lithium-ion batteries. In particular, high interfacial contact resistance between the metal and the solid electrolyte restricts the movement of metal cations, presenting a limitation that leads to reduced overall battery efficiency and lifespan. The problem to be solved
[0003] The present invention was conceived to solve the aforementioned problem, and a modified carbon black coating layer with improved sodium wettability according to a preferred embodiment of the present invention reduces the sheet resistance between sodium metal and a solid electrolyte, and by reducing the sheet resistance, can improve the electrochemical performance of a sodium secondary battery. means of solving the problem
[0004] To achieve the above technical problem, a method for manufacturing a modified carbon black coating layer according to a preferred embodiment of the present invention comprises the step of manufacturing modified carbon black by heat-treating carbon black powder in air (S01);
[0005] A step of preparing a modified carbon black slurry by mixing modified carbon black powder and a solvent (S02); and
[0006] It may include the step (S03) of spraying the modified carbon black slurry onto the surface of a substrate to form a modified carbon black coating layer.
[0007] Through the heat treatment step above, at least one of the chemical bonds among OH, CH, CO, and CC on the surface of the carbon black coating layer can be removed.
[0008] The above description may be a solid electrolyte or a cathode material.
[0009] The above solid electrolyte may include, but is not limited to, a beta-alumina (BA) / yttria-stabilized zirconia (YSZ) composite.
[0010] The contact angle and sheet resistance between the above-mentioned modified carbon black coating layer and the metal containing sodium (Na) can be reduced compared to the contact angle and sheet resistance of the unmodified carbon black coating layer.
[0011] The contact angle between the solid electrolyte and the metal may be 60° or less at 150°C.
[0012] The above sheet resistance is 3.3 Ω·cm at 190 ℃ 2 This is less than or equal to the unmodified carbon black coating layer and may be reduced to 50% or less.
[0013] The thickness of the carbon black coating layer may be in the range of 10 to 200 μm.
[0014] The above solvent may include any one selected from water, methanol, ethanol, isopropyl alcohol, butanol, and mixtures thereof.
[0015] To achieve the above technical problem, a solid electrolyte according to a preferred embodiment of the present invention may include a solid electrolyte having a modified carbon black coating layer formed by the manufacturing method described above.
[0016] To achieve the above technical objective, a negative electrode for a secondary battery according to a preferred embodiment of the present invention may include a negative electrode for a secondary battery having a modified carbon black coating layer formed by the manufacturing method described above. Effects of the invention
[0017] According to the present invention as described above, the invention relates to a method for manufacturing a modified carbon black coating layer according to a preferred embodiment of the present invention, which may include the step of heat-treating carbon black powder in air to produce modified carbon black powder, and then coating a slurry prepared by mixing the modified carbon black powder with a solvent such as isopropyl alcohol onto the surface of a solid electrolyte disk. The modification of the carbon black is characterized by the removal of chemical bonds such as OH, CH, CO, and CC on the surface of the carbon black, thereby significantly improving wettability with sodium metal. This modified carbon black coating layer reduces the sheet resistance between the sodium metal and the solid electrolyte and provides long-term stability. The modified carbon black coating layer according to a preferred embodiment of the present invention can be applied to the solid electrolyte of a sodium secondary battery or the negative electrode of a sodium secondary battery, and can significantly improve electrochemical properties at the solid electrolyte-sodium metal interface.
[0018] The effects of the present invention are not limited to those mentioned above, and include other effects that are clearly understood by a person skilled in the art from the description throughout the specification but are not explicitly mentioned. Brief explanation of the drawing
[0019] Figure 1 is a thermogravimetric analysis (TGA) result for a modified carbon black coating layer according to one embodiment of the present invention. Figure 2 is an X-ray diffraction (XRD) pattern result for a modified carbon black coating layer and an unmodified carbon black coating layer according to one embodiment of the present invention. Figure 3 is an FT-IR spectra result for a modified carbon black coating layer and an unmodified carbon black coating layer according to one embodiment of the present invention. FIG. 4 is a high-magnification scanning electron microscope (SEM) image of a modified carbon black coating layer and an unmodified carbon black coating layer according to one embodiment of the present invention, (a) Comparative Example 1, (b) Example 1, and (c~d) cross-sections of Example 1 (c: high magnification, d: low magnification). FIG. 5 is a digital image showing the behavior of sodium droplets at 150°C for (a) Comparative Example 1, (b) Comparative Example 2, and (c) Example 1 of the present invention. FIG. 6 is a comparison result of (a) Electrochemical Impedance Spectroscopy (EIS) profile, (b) Distribution of Relaxation Times (DRT) plot, and (c) sheet resistance calculated from DRT fitting for a modified carbon black coating layer (Example 1), an unmodified carbon black coating layer (Comparative Example 1), and a case without a coating layer (Comparative Example 2) according to one embodiment of the present invention. FIG. 7 shows (a) a galvanodynamic sweep evaluation, (b) a galvanostatic Na plating / removal profile at 1-minute intervals at increasing current densities, and (c) a comparative analysis of sheet resistance based on EIS, galvanodynamic sweep, and galvanostatic cycling results for a modified carbon black coating layer (Example 1), an unmodified carbon black coating layer (Comparative Example 1), and a case without a coating layer (Comparative Example 2) according to one embodiment of the present invention. FIG. 8 shows the results of galvanostatic cycling for a sodium symmetry cell at 190°C for 250 hours for a modified carbon black coating layer (Example 1), an unmodified carbon black coating layer (Comparative Example 1), and a case without a coating layer (Comparative Example 2) according to one embodiment of the present invention. Specific details for implementing the invention
[0020] Hereinafter, preferred embodiments of the present invention will be described in detail with reference to the attached drawings. The advantages and features of the present invention and the methods for achieving them will become clear by referring to the embodiments described below in detail together with the attached drawings. However, the present invention is not limited to the embodiments disclosed below but can be implemented in various different forms. These embodiments are provided merely to ensure that the disclosure of the present invention is complete and to fully inform those skilled in the art of the scope of the invention, and the present invention is defined only by the scope of the claims. Throughout the specification, the same reference numerals refer to the same components.
[0021] Unless otherwise defined, all terms used herein (including technical and scientific terms) may be used in a meaning commonly understood by those skilled in the art to which the present invention pertains. Furthermore, terms defined in commonly used dictionaries are not to be interpreted ideally or excessively unless explicitly and specifically defined otherwise. The terms used herein are for describing embodiments and are not intended to limit the present invention. In this specification, the singular form includes the plural form unless specifically stated otherwise in the text.
[0022] As used in the specification, "comprises" and / or "comprising" do not exclude the presence or addition of one or more other components, steps, actions, and / or elements to the mentioned components, steps, actions, and / or elements.
[0024] Modified carbon black with improved sodium wettability and method for manufacturing the same
[0025] A method for manufacturing a modified carbon black coating layer according to one embodiment of the present invention may include the step (S01) of manufacturing modified carbon black by heat-treating carbon black powder in air.
[0026] The above heat treatment temperature can be set in the range of 250 to 600 ℃, specifically in the range of 350 to 450 ℃, and this may be suitable for effectively removing or reducing chemical bonds (e.g., at least one of OH, CH, CO, and CC) on the surface of carbon black.
[0027] The above heat treatment time can be adjusted within a range of 10 to 24 hours, and this time range is intended to optimize surface modification and stabilize the physical and chemical properties of the carbon black coating layer.
[0029] Afterwards, a step (S02) of preparing a modified carbon black slurry by mixing the modified carbon black powder and a solvent may be performed.
[0030] The above solvent may specifically include any one selected from water, methanol, ethanol, isopropyl alcohol, butanol, and mixtures thereof, and in one embodiment may include isopropyl alcohol, but is not limited thereto.
[0031] In the mixing process of the above S02, a temperature higher than the boiling point of the solvent is maintained to form a uniform slurry, which may facilitate the removal of the solvent in a subsequent manufacturing process.
[0032] The mixed carbon black slurry can be homogeneously mixed using a swing plenary mixer or a similar device.
[0034] Afterwards, a step (S03) of forming a modified carbon black coating layer by spraying the modified carbon black slurry onto the surface of a substrate may be performed.
[0035] The above description may be a solid electrolyte or negative electrode material for a secondary battery.
[0036] The above-mentioned solid electrolyte is a material having sodium ion conductivity, and any type that ensures sodium ion conductivity suitable for use in sodium secondary batteries can be used without limitation; in one embodiment, it may include a beta-alumina (BA) / yttria-stabilized zirconia (YSZ) composite. This can improve the performance of the sodium secondary battery by providing low sheet resistance and excellent chemical resistance. However, the solid electrolyte is not limited thereto, and other types of sodium ion conductive materials may also be utilized.
[0037] The above cathode material may include metallic sodium, sodium alloy, or carbon-based materials, and various material combinations to improve interfacial compatibility with sodium may be used without limitation. When the modified carbon black coating layer is provided on the surface of the cathode, it can reduce the contact angle with sodium metal and reduce sheet resistance, thereby providing an effect of reducing sheet resistance.
[0039] The modified carbon black coating layer formed through the heat treatment process described above can reduce the interfacial contact angle with sodium metal, reduce sodium sheet resistance, and effectively reduce sheet resistance.
[0041] The contact angle and sheet resistance between the modified carbon black coating layer and the metal containing sodium (Na) are reduced compared to those of the unmodified carbon black coating layer, which can increase sodium wettability (sodiophilicity). This characteristic is a result of improved interfacial compatibility with sodium due to the removal of surface chemical bonds (OH, CH, CO, and CC) during the modification process, which can increase adhesion to the sodium metal and enhance electrochemical performance.
[0042] Specifically, the contact angle can be reduced to 60° or less at 150°C.
[0043] The above sheet resistance is 3.3 Ω·cm at 190 ℃2 It can be reduced to below this level. For example, the sheet resistance of an unmodified carbon black coating layer is approximately 6.6 Ω·cm. 2 However, the sheet resistance of the modified carbon black coating layer is approximately 3.3 Ω·cm 2 Therefore, a reduction in sheet resistance of approximately 50% can be achieved. This improves the electrochemical performance of the sodium secondary battery and can provide lower sheet resistance and efficient energy storage characteristics.
[0045] The thickness of the carbon black coating layer may be in the range of 10 to 200 μm, specifically 70 to 150 μm, and in one embodiment 100 μm, but is not limited thereto. Such a thickness is suitable for ensuring effective interfacial contact between sodium metal and solid electrolyte, reducing sheet resistance, and reducing sheet resistance. However, the thickness of the carbon black coating layer of the present invention may be adjusted according to the design purpose and application field and is not limited to the above range.
[0047] The solid electrolyte having a modified carbon black coating layer formed by the manufacturing method described above can be suitably used as a solid electrolyte for secondary batteries, such as a sodium secondary battery or a lithium secondary battery. The solid electrolyte has characteristics that reduce sheet resistance with sodium metal and improve the long-term stability and efficiency of the battery. Therefore, the solid electrolyte of the present invention can be utilized as a key component to maximize the performance of a sodium secondary battery.
[0049] Furthermore, the solid electrolyte formed with a modified carbon black coating layer prepared by the above-described manufacturing method can be suitably used as a negative electrode for a secondary battery, such as a sodium secondary battery or a lithium secondary battery. The modified carbon black coating layer of the present invention can improve the electrochemical performance of the negative electrode by reducing the contact angle with sodium metal and lowering the sheet resistance. At the same time, by reducing the sodium sheet resistance, the efficiency and stability of the battery can be simultaneously improved. Therefore, the solid electrolyte of the present invention can provide excellent effects as a negative electrode component of a sodium secondary battery.
[0051] The present invention will be explained in more detail below using embodiments and comparative examples. However, the following embodiments and comparative examples are for illustrating the present invention and the scope of the present invention is not limited thereto.
[0053] Example 1: Solid electrolyte coated with modified carbon black with improved sodium wettability
[0054] 1-1) Preparation of Modified Carbon Black Powder
[0055] First, modified carbon black powder was prepared by heat-treating carbon black powder (HiBlack170, Orion Engineered Carbons) in air at 400°C for 12 hours. Through this heat treatment process, OH, CH, CO, and CC bonds on the surface of the carbon black coating layer were reduced.
[0056] 1-2) Preparation of Modified Carbon Black Slurry
[0057] Modified carbon black powder and isopropyl alcohol (99.9%, Daejeong, South Korea) were mixed in a mass ratio of 1:10. The mixture was uniformly dispersed by stirring it in a swing plenary mixer at 600 rpm for 10 minutes using three 5 mm YSZ balls to prepare a modified carbon black slurry (ball milling treatment). During the process of preparing the modified carbon black slurry, the temperature of the hot plate was maintained between 70°C and 300°C to facilitate solvent removal in subsequent steps.
[0058] 1-3) Preparation of a modified carbon black coating layer
[0059] Next, using a rechargeable airbrush, the modified carbon black slurry is applied to a solid electrolyte disc (3 cm in diameter). 2 A porous carbon black coating layer was obtained by spraying it onto the surface of the material. At this time, the thickness of the modified carbon black coating layer is approximately 100 μm.
[0061] Comparative Example 1: Solid electrolyte coated with unmodified raw carbon black
[0062] Instead of using the modified carbon black coating layer of Example 1, raw carbon black powder (HiBlack170, Orion Engineered Carbons) without heat treatment was used, and a solid electrolyte with a raw carbon black coating layer formed was prepared using the same method as in Example 1.
[0064] Comparative Example 2: Solid electrolyte not coated with carbon black
[0065] A solid electrolyte disc with no carbon black coating layer formed at all was used.
[0067] Experimental Example 1: Analysis of Modified Carbon Black Coating Layer
[0068] Figure 1 is a thermogravimetric analysis (TGA) result for a modified carbon black coating layer according to one embodiment of the present invention.
[0069] Referring to Figure 1, the thermogravimetric analysis (TGA) results show the mass change during heating from 25 °C to 800 °C at a rate of 10 °C / min in an air atmosphere. As a result, a rapid mass reduction was observed at temperatures above approximately 500 °C, and it was confirmed that complete combustion was reached at temperatures above 639 °C. This implies that the thermal stability of carbon black is lost at high temperatures and it decomposes due to oxidation. Through this, it was confirmed that performing heat treatment at a temperature of approximately 400 °C is the optimal condition for selectively removing unnecessary chemical bonds while maintaining the main physical properties of carbon black.
[0071] Figure 2 is an X-ray diffraction (XRD) pattern result for modified carbon black powder and unmodified carbon black powder according to one embodiment of the present invention.
[0072] Referring to FIG. 2, a comparison of the XRD patterns of modified carbon black (Example 1) and unmodified raw carbon black (Comparative Example 1) confirms that the crystal structure of the carbon black did not change significantly even after heat treatment. This indicates that the heat treatment process is effective in improving surface properties while maintaining the structural integrity of the material.
[0074] Figure 3 is an FT-IR spectra result for modified carbon black powder and unmodified carbon black powder according to one embodiment of the present invention.
[0075] Referring to FIG. 3, the FT-IR spectra of modified carbon black (Example 1) and unmodified raw carbon black (Comparative Example 1) were analyzed. As a result, after heat treatment at 400 °C for 12 hours, the modified carbon black (Example 1) subjected to heat treatment reached ~3400 cm⁻¹ -1 , ~2900 cm -1 , ~1600 cm -1 and ~1200 cm -1It can be confirmed that the chemical bond peaks corresponding to OH bonds, CH bonds, C=O bonds, and CO or CC bonds, respectively, have decreased in size at the wavelength. The decrease in OH bonds may indicate a decrease in moisture content after heat treatment. Through this, it can be confirmed that at least some of the chemical bonds on the carbon black surface have been removed during the modification process through heat treatment according to Example 1 of the present invention.
[0077] FIG. 4 is a high-magnification scanning electron microscope (SEM) image according to one embodiment of the present invention, showing (a) unmodified raw carbon black powder, (b) modified carbon black powder, and (c~d) cross-sections of a modified carbon black coating layer (Example 1) (c: high magnification, d: low magnification).
[0078] Referring to Figures 4(a~d), it can be seen that the modified carbon black coating layer has a porous structure having macropores with diameters ranging from hundreds of nanometers to tens of micrometers, and it can also be confirmed that the modified carbon black coating layer is uniformly formed with a thickness of about 100 μm on the solid electrolyte disk.
[0080] Experimental Example 2: Evaluation of Sodium Wetness
[0081] The effect of the carbon black layer on sodium wettability was evaluated by contacting a small amount of sodium metal to a solid electrolyte disk and measuring the contact angle.
[0083] FIG. 5 is a digital image showing the behavior of sodium droplets at 150°C for (a) Comparative Example 1, (b) Comparative Example 2, and (c) Example 1 of the present invention.
[0084] Referring to FIG. 5, the beta-alumina (BA) / yttria-stabilized zirconia (YSZ) solid electrolyte exhibits inherent sodium wettability. However, in cases where a carbon black coating is not applied, such as in Comparative Example 2, the contact area with sodium is limited, the contact angle may be approximately 130°, and effective wettability is not observed. Furthermore, in the case of Comparative Example 1, it can be confirmed that the wettability with sodium was not sufficiently improved because heat treatment was not performed. On the other hand, in Example 1, a modified carbon black coating layer with chemical bonds (functional groups) removed through a heat treatment process was applied, which significantly improved sodium wettability. Sodium spread uniformly across the entire surface of the carbon layer, and the contact angle decreased to 60° or less. Through this, it can be confirmed that surface compatibility with metallic sodium was significantly improved.
[0086] Experimental Example 3: Evaluation of Electrical Properties of Modified Carbon Black Coating Layer
[0087] To evaluate the electrical characteristics of the modified carbon black coating layer, the sheet resistance of each sample was measured using a sodium (Na) symmetry cell operating at 190 °C. Sheet resistance was analyzed using electrochemical impedance spectroscopy (EIS) with an SP240 instrument, BioLogic, USA, applying a voltage amplitude of 10 mV over a frequency range of 1 MHz to 0.01 Hz, thereby confirming the effect of the modified carbon black coating layer on the sheet resistance between the sodium metal and the electrolyte. Additionally, current sweeping was performed at ±50 mA cm⁻¹ -2 Up to 10 mA s -1 The resistance per unit area was measured while increasing the current density at a rate of ±3.33 to ±50 mA cm⁻¹ under constant current conditions. -2 Tests were conducted at various current densities up to, and each stage was maintained for 1 minute.
[0088] Long-term cycle performance evaluation was conducted at 190 ℃ at 10, 20, and 30 mA cm⁻¹. -2After cycling for a total of 15 hours with 5 cycles each at a current density of , 40 mA cm -2 Cycling was performed for more than 200 hours under constant current conditions. The cycling test was conducted using a battery test system (LAND-CT3002AU, LANDT Instrument, USA).
[0090] FIG. 6 is a comparison result of (a) Electrochemical Impedance Spectroscopy (EIS) profile, (b) Distribution of Relaxation Times (DRT) plot, and (c) sheet resistance calculated from DRT fitting for a modified carbon black coating layer (Example 1), an unmodified carbon black coating layer (Comparative Example 1), and a case without a coating layer (Comparative Example 2) according to one embodiment of the present invention.
[0091] Referring to Fig. 6(a), the sheet resistance of the sample is 3.3 Ω·cm at 190 ℃. 2 (Example 1), 6.6 Ω·cm 2 (Comparative Example 1) and 45.6 Ω·cm 2 Each was measured as (Comparative Example 2). Through these results, it can be confirmed that the modified carbon black coating layer (Example 1, red) exhibited the lowest sheet resistance, and that the sheet resistance was significantly reduced compared to Comparative Examples 1 and 2, effectively improving the transmission of sodium ions. Referring to Figures 6(b-c), the sheet resistance of each sample can be quantitatively compared. The modified carbon black coating layer (Example 1) exhibited the lowest sheet resistance, which suggests that the chemical bonds (functional groups) removed during the heat treatment process improved the transmission path of sodium ions and significantly enhanced electrochemical performance. On the other hand, Comparative Examples 1 and 2 exhibited relatively high sheet resistance, which clearly demonstrates the effect of heat treatment and the application of the coating layer on sheet resistance. Therefore, it can be confirmed that the modified carbon black coating layer of the present invention is effective in increasing sodium ion transmission efficiency and reducing sheet resistance.
[0093] FIG. 7 shows (a) a galvanodynamic sweep evaluation, (b) a galvanostatic Na plating / removal profile at 1-minute intervals at increasing current densities, and (c) a comparative analysis of sheet resistance based on EIS, galvanodynamic sweep, and galvanostatic cycling results for a modified carbon black coating layer (Example 1), an unmodified carbon black coating layer (Comparative Example 1), and a case without a coating layer (Comparative Example 2) according to one embodiment of the present invention.
[0094] Referring to Fig. 7(a), in the galvanodynamic sweep evaluation performed at 190 °C with various current densities, Example 1 maintained a stable and low overvoltage, whereas Comparative Examples 1 and 2 exhibited unstable overvoltage behavior, indicating that sodium ion transport was not smooth. Referring to Fig. 7(b), in the results of galvanostatic Na plating and removal experiments performed at 1-minute intervals at increasing current densities, Example 1 maintained stable performance despite repeated plating / removal, whereas Comparative Examples 1 and 2 showed intensified overvoltage and electrical instability as the current density increased. Referring to Fig. 7(c), as a result of combining EIS, galvanodynamic sweep, and galvanostatic cycling data, it can be seen that Example 1 exhibited low sheet resistance and simultaneously significantly improved interface characteristics.
[0096] Experimental Example 4: Cell Stability Evaluation
[0097] FIG. 8 shows the results of galvanostatic cycling for a sodium symmetry cell at 190°C for 250 hours for a modified carbon black coating layer (Example 1), an unmodified carbon black coating layer (Comparative Example 1), and a case without a coating layer (Comparative Example 2) according to one embodiment of the present invention.
[0098] Referring to FIG. 8, the modified carbon black coating layer (Example 1) maintained a stable overvoltage during long-term cycling and exhibited excellent durability. In contrast, Comparative Example 1 showed high overvoltage and performance degradation. Comparative Example 2, which lacked a coating layer, failed to maintain performance during long-term cycling due to unstable electrical characteristics from the beginning. This indicates that the modified carbon black coating layer improves interfacial compatibility between the solid electrolyte and sodium metal and ensures long-term stability.
[0100] Although embodiments of the present invention have been described above with reference to the attached drawings, those skilled in the art will understand that the present invention may be implemented in other specific forms without changing its technical concept or essential features. Therefore, the embodiments described above should be understood as illustrative in all respects and not restrictive.
Claims
Claim 1 A method for manufacturing a modified carbon black coating layer comprising: a step of manufacturing modified carbon black by heat-treating carbon black in air (S01); a step of preparing a modified carbon black slurry by mixing the modified carbon black with a solvent (S02); and a step of forming a modified carbon black coating layer by spraying the modified carbon black slurry onto the surface of a substrate (S03); wherein, through the heat-treating step, at least one chemical bond among OH, CH, CO, and CC is removed from the surface of the carbon black, and the contact angle with sodium (Na) metal is reduced compared to a substrate on which the modified carbon black coating layer is not formed or a carbon black coating layer on which the heat treatment is not performed. Claim 2 A method for manufacturing a modified carbon black coating layer according to claim 1, characterized in that the above-mentioned material is a solid electrolyte or a cathode material. Claim 3 A method for manufacturing a modified carbon black coating layer according to claim 2, wherein the solid electrolyte comprises a beta-alumina (BA) / yttria-stabilized zirconia (YSZ) composite. Claim 4 A method for manufacturing a modified carbon black coating layer according to claim 1, characterized in that the sheet resistance between the modified carbon black coating layer and sodium (Na) metal is reduced compared to the sheet resistance of the unmodified carbon black coating layer. Claim 5 A method for manufacturing a modified carbon black coating layer according to claim 1, characterized in that the contact angle of the modified carbon black coating layer is 60° or less at 150°C. Claim 6 In paragraph 4, the sheet resistance is 3.3 Ω·cm at 190 ℃. 2 It is less than or equal to, and this is less than or equal to 50% compared to the unmodified carbon black coating layer. A method for manufacturing a modified carbon black coating layer characterized by a reduction. Claim 7 A method for manufacturing a modified carbon black coating layer according to claim 1, wherein the thickness of the carbon black coating layer is in the range of 10 to 200 μm. Claim 8 A method for preparing a modified carbon black coating layer according to claim 1, wherein the solvent comprises any one selected from water, methanol, ethanol, isopropyl alcohol, butanol, and mixtures thereof. Claim 9 A solid electrolyte having a modified carbon black coating layer formed by the method of any one of claims 1 to 8. Claim 10 A negative electrode for a secondary battery having a modified carbon black coating layer formed by the method of any one of claims 1 to 8.
Citation Information
Patent Citations
Device and method for preparing slurry and coating a substrate with the slurry
KR1020210006918A
Thermally modified carbon blacks for various typeapplications and a process for producing same
KR1020060123120A
Use of carbon metal composites for surface treatment to improve sodium wettability in solid-state electrolytes
KR1020240122527A
Solid electrolyte for sodium secondary battery, sodium secondary battery having the same and method of manufacturing for solid electrolyte for sodium secondary battery
KR1020240129849A
